Microanatomical studies of the trachea in pigeon - S. Rajathi; S. Muthukrishnan; Geetha Ramesh; S. Paramasivan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Trachea was collected from two adult male and female pigeons of Tirunelveli district. The aim of the study was to find out the microanatomical details of trachea in granivore birds. Trachea was lined by a pseudostratified ciliated columnar epithelium. Lamina propria was made up of loose connective tissue and contained alveolar mucous glands. The submucosa contained elastic fibres and was found related to perichondrium of cartilaginous rings. The cartilaginous rings were flattened in cross section. Overlapping of cartilaginous rings was prominent. Thin tunica adventitia covered the cartilaginous rings. Trachealis muscle was absent.